Os desafios do estágio supervisionado I no ensino de Ciências para graduandos da licenciatura integrada em Biologia e Química da Universidade Federal do Oeste do Pará - JATY, Eurilene Prata (Universidade Federal do Oeste do Pará, 2024)
Considering that in undergraduate courses the Supervised Internship is important for the initial training of teachers, as it provides the graduate with the mastery of theoretical and practical tools essential to the implementation of their functions, we researched The challenges of Supervised Internship I in Science Teaching for undergraduates of the Integrated Degree in Biology and Chemistry of the Federal University of Western Pará to analyze the representations and perceptions of the experiences of Supervised Internship I among students of an undergraduate class of Degree in Biology and Chemistry of UFOPA. To this end, we sought to establish the class profile in terms of age and place of birth; to identify the profiles of the schools where the internship took place in terms of their location, teaching modality and whether they attend only Elementary Education or Elementary. In view of this, we verified that fear, insecurity, and uncertainty about their ability to exercise their profession well is what worries these trainees the most, which imposes the observation that it is notorious that they always need to innovate, rethink old teaching-learning methods and create different paths in the training processes of the students.